Halal Economy as a Driver of Global Development: Literature Review VoS Viewer - Trimulato; Asyraf Mustamin (Universitas Darunnajah, 2025)
The global rise of the halal economy has positioned it as a critical component in advancing inclusive and sustainable global development. This study aims to systematically explore the trends, challenges, and opportunities in halal economic research, while mapping key themes and research gaps using a bibliometric approach. Employing a Systematic Literature Review (SLR) combined with VOSviewer bibliometric analysis, this research analyzes 97 academic publications from 2014 to 2024 sourced via the Publish or Perish software. The findings reveal a significant growth trajectory in halal economy-related research, with dominant themes encompassing halal industry development, sustainability, Islamic finance, and halal tourism. The analysis also highlights Indonesia’s central role in halal economic scholarship and underscores the increasing integration of halal values with the Sustainable Development Goals (SDGs). However, persistent challenges such as fragmented global halal standards and low halal literacy in several regions remain critical barriers to inclusive global expansion. This study offers strategic insights for policymakers to foster a harmonized global halal ecosystem by strengthening regulations, supporting innovation, and enhancing cross-border cooperation. The results also provide a roadmap for future research to align halal economic practices with sustainable and ethical global development frameworks.